Students Tele-All: Self-Efficacy and Self-Reflection as Measures of Student Success in Telepractice Training - Amanda Worek; Kathryn K. Sabo; Emily Z. Eddy; Laura Plummer; Jane Baldwin; Patricia A. Reidy; Mary W. Hildebrand; Mary Riotte; John Wong (MDPI AG, 2022)
With an increasing demand for telepractice services, the need for telepractice education is more important than ever. In addition to learning how to deliver these services, certain clinical and technological skills learned through telepractice apply more broadly to in-person care. Evaluating students' abilities to master these skills is necessary to ensure clinical skill competence. We utilized self-efficacy ratings and self-reflections to determine student growth after hands-on telepractice training among nursing, occupational therapy, physical therapy, and speech-language pathology students. Students across disciplines demonstrated growth in all measured skill areas and reported overall increased confidence. Students with less prior telepractice experience reported greater increased confidence in seven measured competency areas than students with more prior telepractice experience. The number of completed sessions at the end of student placements was correlated with increased confidence for one measured skill area. Regardless of whether or not students had prior experience when starting their placement, as the number of telepractice sessions completed increased, thus did students' confidence levels. The results of this study support telepractice as a viable clinical education tool for student growth and the use of self-efficacy and self-reflection as valuable tools for monitoring the effectiveness of telepractice clinical learning activities.